6c-13d-9c+5d=

Simple and best practice solution for 6c-13d-9c+5d= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6c-13d-9c+5d= equation:


Simplifying
6c + -13d + -9c + 5d = 0

Reorder the terms:
6c + -9c + -13d + 5d = 0

Combine like terms: 6c + -9c = -3c
-3c + -13d + 5d = 0

Combine like terms: -13d + 5d = -8d
-3c + -8d = 0

Solving
-3c + -8d = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '8d' to each side of the equation.
-3c + -8d + 8d = 0 + 8d

Combine like terms: -8d + 8d = 0
-3c + 0 = 0 + 8d
-3c = 0 + 8d
Remove the zero:
-3c = 8d

Divide each side by '-3'.
c = -2.666666667d

Simplifying
c = -2.666666667d

See similar equations:

| x^2+Y^2-6x+4y+13=0 | | 1 = q2 | | 18y-22=3x-2 | | 12x-3x*2=0 | | 12r+s+18r+19s= | | 3v-4=3v+7 | | 11x-(7+5x)= | | 17x-8=81 | | -8(5r+1)=32 | | (-8x+2)+(-10x-7)= | | 2x-31=3(x-2) | | X^2+(6k+4)X+3=0 | | 6+30x=20x+24 | | 48*64=12x*16x | | 50-3s=2 | | 8k+2=15k-12 | | -5(7+7x)=245 | | 8k+8=17k-19 | | 10k+11=14k-9 | | 7y=y+48 | | 13=1+6x+6 | | 18*18=24x*6x | | t^2=-10t+11 | | 12*12=16x*4x | | -3(8x-1)=2x-5 | | 6x^2+8x=128 | | 7[1-2x]-3[x-1]= | | 3=2(6)+b | | 221.9352=19.468*w | | x^2+8x+16=-1 | | 6x^4-30x^2+20=0 | | 8(X-2)=72 |

Equations solver categories